miR-9 and NFATc3 Regulate Myocardin in Cardiac Hypertrophy - Wang, Kun (American Society for Biochemistry and Molecular Biology, 2010)
Myocardial hypertrophy is frequently associated with poor clinical outcomes including the development of cardiac systolic and diastolic dysfunction and ultimately heart failure. To prevent cardiac hypertrophy and heart failure, it is necessary to identify and characterize molecules that may regulate the hypertrophic program. Our present study reveals that nuclear factor of activated T cells c3 (NFATc3) and myocardin constitute a hypertrophic pathway that can be targeted by miR-9. Our results show that myocardin expression is elevated in response to hypertrophic stimulation with isoproterenol and aldosterone. In exploring the molecular mechanism by which myocardin expression is elevated, we identified that NFATc3 can bind to the promoter region of myocardin and transcriptionally activate its expression. Knockdown of myocardin can attenuate hypertrophic responses triggered by NFATc3, suggesting that myocardin can be a downstream mediator of NFATc3 in the hypertrophic cascades. MicroRNAs are a class of small noncoding RNAs that mediate post-transcriptional gene silencing. Our data reveal that miR-9 can suppress myocardin expression. However, the hypertrophic stimulation with isoproterenol and aldosterone leads to a decrease in the expression levels of miR-9. Administration of miR-9 could attenuate cardiac hypertrophy and ameliorate cardiac function. Taken together, our data demonstrate that NFATc3 can promote myocardin expression, whereas miR-9 is able to suppress myocardin expression, thereby regulating cardiac hypertrophy.